Infrared Spectral Composition of Rose Oil From Turkey - BARDAKCI, B.; SECILMIS, H.; YILMAZER, M. (Asian Journal of Chemistry, 2010)
This work presents an approach to analyze the chemical structure of rose oil by means of infrared spectroscopy. It is shown that the main components of the rose essential oil can be ascertained through FTIRATR technique and pellets with KBr, using spectral information from the pure standard substances. Spectroscopic analysis is based on the characteristic vibrational frequencies of the standard substances and essential oil. Basically, these techniques define the characteristic bands of rose oil and recognize the main components of essential rose oil by comparing the spectroscopic data of pure standards to that of rose oil. The highest percentages contents of essential oil are chosen to investigate unique wavenumbers. IR data results give valuable information to interpret the key bands of rose essential oil. Main components of rose oil obtained from IR spectroscopy are good agreement with those by GC-MS analysis.